2012
DOI: 10.1212/wnl.0b013e31823fcd26
|View full text |Cite
|
Sign up to set email alerts
|

Randomized clinical trial for apogeotropic horizontal canal benign paroxysmal positional vertigo

Abstract: NCT00810641.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
102
1
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 127 publications
(114 citation statements)
references
References 29 publications
8
102
1
3
Order By: Relevance
“…83,194,198 Geotropic: Nystagmus usually beats toward the affected ear. Apogeotropic: Nystagmus beats away from the affected ear.…”
Section: Technique or Circumstance Conclusion Regarding The Affected Earmentioning
confidence: 99%
“…83,194,198 Geotropic: Nystagmus usually beats toward the affected ear. Apogeotropic: Nystagmus beats away from the affected ear.…”
Section: Technique or Circumstance Conclusion Regarding The Affected Earmentioning
confidence: 99%
“…Beyond the Gufoni and BBQ maneuvers, two other procedures were used in our cupulolithiasis patients; the HSM (in three patients) and forced prolonged position 20 . Kim J-S et al 12 showed in 157 patients that both the Gufoni and HSM maneuvers were equally effective in the treatment of HC-BPPV cupulolithiasis, with success rates of 73.1% and 62.3%, respectively. Oh Sy, et al 25 compared the efficacy of HSM versus the modified Semont maneuver in 103 patients, concluding that the former is more effective (37.3% versus 17.3%) in the resolution of vertigo/nystagmus.…”
Section: Resultsmentioning
confidence: 99%
“…In addition to its higher success rate, the Gufoni maneuver 15 is not only less time consuming 12 but also easier to perform than the BBQ 360° maneuver in obese or elderly persons and in patients with cervical pain and stiffness 9,17 . It is worth mentioning that one third of our patients were over 70 years old.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Though positional nystagmus has many of the more important clinical characteristics of the horizontal canal BPPV by canalithiasis -latency, geotropic direction and finally exhaustion -its prolongued duration to both sides and the lack of response to Gufoni maneuver, which has an evidence-based efficacy [4,5], guided us towards an atypical form of HC BPPV and thus we requested neuroimaging studies [6].…”
Section: Discussionmentioning
confidence: 99%